1996
DOI: 10.1093/oxfordjournals.annonc.a010761
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C plus vindesine plus etoposide (MEV) versus mitomycin C plus vindesine plus cisplatin (MVP) in stage IV non-small-cell lung cancer: A phase III multicentre randomised trial

Abstract: In the present study, no significant differences were observed in response rate, survival or palliation of symptoms between the MEV and MVP regimens, while toxicity was significantly more frequent and severe with MVP. Thus, MEV should be considered a reasonable alternative to the MVP regimen in the treatment of stage IV NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Other trials showed similar response rates and survival, and less toxicity in patients treated with nonplatinum-based schedules compared to platinum-containing combinations (Gatzemeier et al, 1991;Gridelli et al, 1996;Georgoulias et al, 2001;Sculier et al, 2002). A recently published study compared four platinum-based regimens for advanced NSCLC (cisplatin with either paclitaxel, gemcitabine, or docetaxel, and carboplatin with paclitaxel), and showed no difference in survival (the median survival was 7.9 months for all patients) and response rate (19% for all patients).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other trials showed similar response rates and survival, and less toxicity in patients treated with nonplatinum-based schedules compared to platinum-containing combinations (Gatzemeier et al, 1991;Gridelli et al, 1996;Georgoulias et al, 2001;Sculier et al, 2002). A recently published study compared four platinum-based regimens for advanced NSCLC (cisplatin with either paclitaxel, gemcitabine, or docetaxel, and carboplatin with paclitaxel), and showed no difference in survival (the median survival was 7.9 months for all patients) and response rate (19% for all patients).…”
Section: Discussionmentioning
confidence: 95%
“…Phase III studies have reported similar response rates and overall survival in cisplatin and noncisplatin-based regimens. However, in the majority of these trials the nonplatinum regimens had a more favourable toxicity profile (Gatzemeier et al, 1991;Gridelli et al, 1996;Georgoulias et al, 2001;Kosmidis et al, 2002;Sculier et al, 2002).…”
mentioning
confidence: 99%
“…17 Despite modern antiemetic and hydration regimens, cisplatin has substantial side effects that limit its use. 18,19 There are several ways to circumvent cisplatin-induced toxicities, including omitting cisplatin and replacing it with a cytotoxic drug with similar activity. One such regimen, paclitaxel plus gemcitabine, has been shown in a phase II study to produce a major response rate of 24% with acceptable toxicity.…”
mentioning
confidence: 99%
“…However, combination chemotherapy containing CDDP has significant toxicities, including severe nausea, vomiting and renal toxicity requiring adequate hydration, which increases the difficulty in the treatment of the elderly or outpatients. In previous randomised studies, CDDP-containing combinations have proved more toxic than those without cisplatin (Luedke et al, 1990;Gridelli et al, 1996;Georgoulias et al, 2001). Carboplatin is a platinum without the toxic disadvantages of CDDP; however, this agent still causes nausea, vomiting and myelosuppression.…”
mentioning
confidence: 99%